English and Arabic Subordinate Adverbial Clauses and Subordinators: A Contrastive Study (Journal of the College of Basic Education, 2025)
This study explores the English subordinate adverbial clauses and adverbial subordinators and compares them with their Arabic counterparts. The problems of This study tries to investigate, Accordingly, it hypothesizes that (1) Whether the English subordinate adverbial clauses have corresponding Arabic counterparts and (2) Whether the English adverbial subordinators have corresponding Arabic equivalents. The present study tackles the problem of the absence of corresponding Arabic equivalents to the English subordinate adverbial clauses and subordinators. This could pose a problem to translators. This study limits itself to the subordinate adverbial clauses as they appear within the context of complex sentences. Other types of subordinate clauses, nominal or adjectival, are beyond the scope of this study. This study is hoped to be of some theoretical and practical value to those concerned with syntactic structures and translation. The methodology adopted in dealing with the subject under investigation is the contrastive approach.